Adsorption and Characterization of Activated Sugarcane Bagasse Using Sodium Hydroxide - Priyanto, Ade; F., Malik; Muhdarina, Muhdarina; A., Awaluddin (Indonesian Journal of Chemical Research, 2021)
Sugarcane Bagasse can be used as an adsorbent both under natural conditions and modified by chemical activation using sodium hydroxide (NaOH). Activation of sugarcane bagasse with NaOH was carried out at variations of 5:1, 10:1, and 20:1 (w/w). The absorption ability of bagasse adsorbent to methylene blue solution was carried out with the parameters of variation of contact time (60, 90, 120, 150, and 180 minutes), adsorbate concentration (20, 30, 40, 50, and 60 ppm) and temperature (30, 40, 50, and 60 oC). The adsorbent's characterization included determining the functional groups using FTIR, morphology, and mass of elements using SEM-EDX, and determining the surface area and volume of adsorbent pores using the BET methods. The highest adsorption percentage results were found in the NASB10:1 adsorbent at 99.50%. The optimum conditions for the NASB10:1 adsorbent are with a contact time of 120 minutes, an adsorbate concentration of 50 ppm and a temperature of 30 oC or 303 K. The NASB10:1 adsorbent has the highest surface area compared to other adsorbents, namely 2.803 m2/g so that it can perform the maximum absorption of methylene blue.